Inorganic nano ceramic coating and preparation method thereof
By preparing silicone modifiers and combining silicon sol and silane, an inorganic nanoceramic emulsion with good anti-aging and anti-bacterial properties is formed, which solves the problem of poor anti-aging and anti-bacterial properties of existing inorganic nanoceramic coatings, and significantly improves the durability and anti-fouling properties of the coating.
Patent Information
- Application Number
- CN202411604128.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing inorganic nanoceramic coatings have poor anti-aging and anti-bacterial properties.
By preparing silicone modifiers, a silicone oil with high hydrogen-containing silicone oil, dodecyl (2-{[2-methoxy-5-(propyl-2-enyl)phenyl]oxy}-2-oxyethylene)dimethylammonium and 4-propyleneoxy-2-hydroxybenzophenone were used to form an inorganic nanoceramic emulsion with good anti-aging and anti-mildehyde and anti-bacterial properties.
It significantly improves the anti-aging and anti-bacterial properties of inorganic nanoceramic coatings, and solves the problems of insufficient durability and anti-fouling performance of the coatings.
Smart Images

Figure CN119119787B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic coatings, and in particular to an inorganic nano ceramic coating and a preparation method thereof. Background Art
[0002] Ceramic coating is a water-based inorganic coating, which was first prepared by the sol-gel method in the 1960s. The sol-gel process was first proposed by German researchers, and coating is one of the most important applications of the sol-gel process. This is because the sol-gel technology can form a three-dimensional network structure of gel using liquid solution on various substrates at relatively low temperatures to form a solid film with a wide range of chemical compositions. As a type of ceramic coating, inorganic nano-ceramic coating has developed rapidly in recent years and is widely used in interior and exterior wall building panels, fireproof material panels, household products, automobile wheels, etc. It has the characteristics of water resistance, alcohol resistance, wear resistance, scratch resistance, and high temperature resistance, and the paint film hardness can reach 4H-6H.
[0003] The Chinese invention patent with publication number CN109266057A discloses a room-temperature curing, super-weather-resistant, high-hardness, and wear-resistant water-based inorganic nano-ceramic coating and a preparation method thereof. The inorganic nano-ceramic coating includes a water-based inorganic nano-ceramic emulsion, a pigment, a filler, a wetting dispersant, a non-stick leveling agent, a thickener, a water-based silicone dispersion, and water. It has the characteristics of high hardness, high wear resistance, super-weather resistance, and room-temperature curing, but its anti-aging and anti-mildew and antibacterial properties are poor. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an inorganic nano-ceramic coating and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] An inorganic nano-ceramic coating comprises the following raw materials in parts by weight:
[0007] Water-based inorganic nano-ceramic emulsion: 50-80 parts,
[0008] Pigment: 0.5-1 part,
[0009] Filling: 8-10 parts,
[0010] Defoaming agent: 0.1-0.5 parts,
[0011] Dispersant: 1-3 parts,
[0012] Wetting agent: 0.2-0.4 parts,
[0013] Film-forming aid: 3-5 parts,
[0014] Deionized water: 20-60 parts;
[0015] The aqueous inorganic nano-ceramic emulsion comprises the following raw materials in parts by weight:
[0016] Silica sol: 20-80 parts,
[0017] Silane: 10-50 parts,
[0018] Silicone modifier: 0.3-0.8 parts,
[0019] Surfactant: 0.5-1 part,
[0020] Deionized water: 30-50 parts;
[0021] The organosilicon modifier is prepared by the following method:
[0022] Toluene was added to the reactor, stirred, and heated to 70-110°C. High hydrogen-containing silicone oil and dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium were added in sequence. Under nitrogen protection, chloroplatinic acid-triphenylphosphine complex was slowly added dropwise. After the addition was completed, the reaction was carried out for 2-6 hours, and the temperature was lowered to 50°C. Then, 4-propyleneoxy-2-hydroxybenzophenone was added, and the temperature was raised to 80-100°C. The reaction was carried out for 4-8 hours. After the reaction was completed, the organic silicon modifier was obtained by vacuum distillation at 110-130°C. The reaction equation is shown as follows:
[0023]
[0024] Among them, m, o, p, and q are natural numbers.
[0025] The mass ratio of the toluene, high hydrogen silicone oil, dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium, chloroplatinic acid-triphenylphosphine complex, and 4-propyleneoxy-2-hydroxybenzophenone is 15:(8-10):(5-7):(0.1-0.3):(3-6).
[0026] The pigment is one of titanium dioxide, lead chrome yellow and iron blue.
[0027] The filler is one or a combination of talcum powder, mica powder and kaolin.
[0028] The defoamer is one of BYK-024 defoamer, TEGO Foamex 830 defoamer and BYK-055.
[0029] The dispersant is one of LD-64190 and LD-6408.
[0030] The wetting agent is Digo 270 wetting agent.
[0031] The film-forming aid is silane coupling agent KH-550.
[0032] The silica sol is acidic silica sol.
[0033] The silane is a combination of one or more of phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
[0034] The surfactant is at least one of the quaternary ammonium cationic surfactants 1831 and OB-2.
[0035] A method for preparing an inorganic nano-ceramic coating comprises the following steps:
[0036] (1) Add silane, surfactant and organosilicon modifier to the stirrer in sequence, stir for 10-20 minutes, and after mixing evenly, form a transparent silane mixed liquid; then add silica sol and stir for 10-30 minutes; slowly raise the temperature to 30-50°C, stir at a constant temperature for 2-8 hours, stop stirring, keep warm at 40°C for 1-4 hours, then add deionized water, mix evenly and cool to room temperature to obtain an inorganic nano-ceramic emulsion;
[0037] (2) The inorganic nano-ceramic emulsion prepared above is mixed with pigment and filler, dispersed at high speed for 20-40 minutes using a high-speed disperser, and then ground using a horizontal sand mill. After grinding, a dispersant, a defoamer, a wetting agent, a film-forming aid and deionized water are added and stirred evenly to obtain an inorganic nano-ceramic coating.
[0038] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:
[0039] (1) The present invention prepares an organic silicon modifier by using high hydrogen silicone oil, dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxydiethyl) dimethyl ammonium and 4-propyleneoxy-2-hydroxybenzophenone, and then mixes it with silica sol and silane to obtain an inorganic nano-ceramic emulsion with good anti-aging and anti-mildew and antibacterial properties.
[0040] (2) The organosilicon modifier prepared by the present invention has both antibacterial and UV aging resistance. The long-chain aliphatic hydrocarbon group on the nitrogen atom in dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium has good lipophilicity and can be inserted into the fungal cell membrane and tightly combined with the hydrophobic groups of the phospholipid molecular layer, thereby disintegrating the skeleton structure of the cell membrane and solving the problem of poor durability of the antibacterial function of the inorganic nano-ceramic coating. The hydroxyl hydrogen on the benzene ring of 4-propyleneoxy-2-hydroxybenzophenone and the adjacent carbonyl oxygen form an intramolecular hydrogen bond to form a chelate ring with a stable conjugated structure, which makes it have good anti-aging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium prepared in Example 1. DETAILED DESCRIPTION
[0042] The invention will be further described below with reference to the embodiments, but the invention is not limited to these embodiments.
[0043] Example 1 Preparation of dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium:
[0044] 120g of chloroacetic acid was added to the reaction bottle, heated to 100℃ to melt, then 100g of 2-methoxy-5-(prop-2-enyl)phenol and 1g of concentrated sulfuric acid (98.3wt%) were added, and then the temperature was raised to 120℃ and the reaction was carried out for 10h. After the reaction, it was washed with deionized water three times (50g of deionized water was used each time), and then dissolved with 20ml of dichloromethane, dried with 40g of anhydrous Na2SO4, and then distilled at 45℃ under reduced pressure for 5h to obtain a light yellow intermediate; 10g of the light yellow intermediate and 30g of dichloromethane were added to the reaction bottle. Add alkane to the reaction flask, slowly add 8g dodecyldimethyl tertiary amine dropwise (dropwise for 5 minutes), reflux for 5 hours after the dropwise addition, then distill under reduced pressure at 40°C for 4 hours, and then recrystallize with acetone / ethanol mixed solution (acetone / ethanol = 9:1 (V / V)), repeat 3 times (each time using 100ml of the mixed solution), and vacuum dry at 60°C for 5 hours to obtain dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium, the hydrogen nuclear magnetic resonance spectrum data of which are as follows: 1 H NMR (300 MHz, DMSO- d 6) δ 6.94 – 6.80 (m, 3H),5.93 (ddt, J= 17.1, 9.7, 7.5 Hz, 1H), 5.21 (ddt, J = 9.7, 2.2, 1.5 Hz, 1H),4.98 (ddt, J = 17.0, 2.3, 1.5 Hz, 1H), 4.52 (s, 2H), 3.84 (s, 3H), 3.49 (t, J = 8.6 Hz, 2H), 3.34 – 3.24 (m, 1H), 3.27 (s, 7H), 1.70 (tt, J = 8.6, 6.2 Hz,2H), 1.44 – 1.18 (m, 5H), 0.98 – 0.82 (m, 3H), 1.51 – 0.98 (m, 11H), 1.24 (s,2H).
[0045] Example 2 Preparation of organosilicon modifier:
[0046] 1500g of toluene was added to the reactor, stirred, and heated to 70°C. 800g of high hydrogen silicone oil and 500g of dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium (prepared in Example 1) were added in sequence. Under nitrogen protection, 10g of chloroplatinic acid-triphenylphosphine complex was slowly added dropwise (dropwise for 2min), and the reaction was completed for 6h. The temperature was lowered to 50°C, and then 300g of 4-propyleneoxy-2-hydroxybenzophenone was added. The temperature was raised to 80°C and the reaction was carried out for 8h. After the reaction was completed, the reaction was carried out under reduced pressure distillation at 110°C for 3h to obtain an organosilicon modifier.
[0047] Example 3 Preparation of organosilicon modifier:
[0048] 1500g of toluene was added to the reactor, stirred, and heated to 90°C. 900g of high hydrogen silicone oil and 600g of dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium (prepared in Example 1) were added in sequence. Under nitrogen protection, 20g of chloroplatinic acid-triphenylphosphine complex was slowly added dropwise (dropwise for 2min), and the reaction was completed for 4h. The temperature was lowered to 50°C, and then 450g of 4-propyleneoxy-2-hydroxybenzophenone was added. The temperature was raised to 90°C and the reaction was carried out for 6h. After the reaction was completed, the organosilicon modifier was obtained by distillation at 120°C under reduced pressure for 2h.
[0049] Example 4 Preparation of organosilicon modifier:
[0050] 1500g of toluene was added to the reactor, stirred, and heated to 110°C. 1000g of high hydrogen silicone oil and 700g of dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethylammonium (prepared in Example 1) were added in sequence. Under nitrogen protection, 30g of chloroplatinic acid-triphenylphosphine complex was slowly added dropwise (dropwise for 2min), and the reaction was completed for 2h. The temperature was lowered to 50°C, and then 600g of 4-propyleneoxy-2-hydroxybenzophenone was added. The temperature was raised to 100°C and the reaction was carried out for 4h. After the reaction was completed, the reaction was carried out under reduced pressure distillation at 130°C for 1h to obtain an organosilicon modifier.
[0051] Example 5 Preparation of Inorganic Nano-Ceramic Coating:
[0052] (1) Add 100 g of silane (phenyltriethoxysilane), 5 g of surfactant (quaternary ammonium cationic surfactant 1831) and 3 g of organosilicon modifier (prepared in Example 2) to a stirrer in sequence, stir for 10 min at a stirring speed of 1000 r / min, and after mixing evenly, a transparent silane mixed liquid is formed; then add 200 g of silica sol (Bate HA2005 acidic silica sol) and stir for 10 min at a stirring speed of 700 r / min; slowly heat to 30°C, stir at a constant temperature for 8 h, stop stirring, keep warm at 40°C for 1 h, then add 300 g of deionized water, mix evenly and cool to room temperature to obtain an inorganic nano-ceramic emulsion;
[0053] (2) 500 g of the inorganic nano-ceramic emulsion prepared above was mixed with 5 g of pigment (titanium dioxide) and 80 g of filler (talcum powder), and dispersed at high speed for 20 min using a high-speed disperser at a speed of 5000 r / min, and then ground for 30 min using a horizontal sand mill. After grinding, 10 g of dispersant (LD-64190), 1 g of defoamer (BYK-024 defoamer), 2 g of wetting agent (Digo 270), 30 g of film-forming aid (silane coupling agent KH-550) and 200 g of deionized water were added and stirred for 20 min to obtain an inorganic nano-ceramic coating.
[0054] Example 6 Preparation of Inorganic Nano-Ceramic Coating:
[0055] (1) Add 300 g of silane (γ-methacryloxypropyltrimethoxysilane), 8 g of surfactant (OB-2) and 5.5 g of organosilicon modifier (prepared in Example 3) to a stirrer in sequence, stir for 15 min at a stirring speed of 900 r / min, and after mixing evenly, form a transparent silane mixed liquid; then add 500 g of silica sol (Bate HA2005 acidic silica sol), stir for 20 min at a stirring speed of 600 r / min; slowly heat to 40°C, stir at a constant temperature for 6 h, stop stirring, keep warm at 40°C for 2.5 h, then add 400 g of deionized water, mix evenly and cool to room temperature to obtain an inorganic nano-ceramic emulsion;
[0056] (2) 650 g of the inorganic nano-ceramic emulsion prepared above was mixed with 8 g of pigment (lead chrome yellow) and 90 g of filler (mica powder), and dispersed at high speed for 30 min using a high-speed disperser at a speed of 4000 r / min, and then ground for 35 min using a horizontal sand mill. After grinding, 20 g of dispersant (LD-6408), 3 g of defoamer (TEGO Foamex 830), 3 g of wetting agent (TEGO 270), 40 g of film-forming aid (silane coupling agent KH-550) and 400 g of deionized water were added and stirred for 30 min to obtain an inorganic nano-ceramic coating.
[0057] Example 7 Preparation of Inorganic Nano-Ceramic Coating:
[0058] (1) Add 500 g of silane (3-glycidyloxypropyltrimethoxysilane), 10 g of surfactant (quaternary ammonium cationic surfactant 1831) and 8 g of organosilicon modifier (prepared in Example 4) to a stirrer in sequence, stir for 20 min at a stirring speed of 800 r / min, and after mixing evenly, a transparent silane mixed liquid is formed; then add 800 g of silica sol (Bate HA2005 acidic silica sol) and stir for 30 min at a stirring speed of 500 r / min; slowly heat to 50°C, stir at a constant temperature for 2 h, stop stirring, keep warm at 40°C for 15 h, then add 500 g of deionized water, mix evenly and cool to room temperature to obtain an inorganic nano-ceramic emulsion;
[0059] (2) 800 g of the inorganic nano-ceramic emulsion prepared above was mixed with 10 g of pigment (iron blue) and 100 g of filler (kaolin), and dispersed at high speed for 40 min using a high-speed disperser at a speed of 3000 r / min, and then ground for 40 min using a horizontal sand mill. After grinding, 30 g of dispersant (LD-64190), 5 g of defoamer (BYK-055), 4 g of wetting agent (DiGao 270), 50 g of film-forming aid (silane coupling agent KH-550) and 600 g of deionized water were added and stirred for 40 min to obtain an inorganic nano-ceramic coating.
[0060] Comparative Example 1
[0061] The method for preparing an inorganic nano-ceramic coating is substantially the same as that of Example 6, except that no organosilicon modifier is added in step (1).
[0062] Comparative Example 2
[0063] A method for preparing an inorganic nano-ceramic coating is substantially the same as that of Example 6, except that the organosilicon modifier added in step (1) is replaced by 2.5 g of high hydrogen silicone oil, 1.6 g of dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium and 1.4 g of 4-propyleneoxy-2-hydroxybenzophenone.
[0064] Comparative Example 3
[0065] The preparation method of an inorganic nano-ceramic coating is basically the same as that of Example 6, except that the organosilicon modifier added in step (1) is replaced by an equal weight of Silok 3300 amino-functional organosilicon prepolymer.
[0066] Comparative Example 4
[0067] The room temperature curing, super weather-resistant, high-hardness and wear-resistant water-based inorganic nano-ceramic coating is prepared by using the raw materials and method of Example 2 in the publication number CN109266057A.
[0068] Comparative Example 5
[0069] A method for preparing an inorganic nano-ceramic coating is substantially the same as that of Example 6, except that the organosilicon modifier added in step (2) is replaced by an equal weight of an organosilicon modifier prepared by the following method:
[0070] Add 1500g of toluene to the reactor, stir, raise the temperature to 90°C, add 900g of high hydrogen silicone oil and 600g of dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium in sequence, and slowly add 20g of chloroplatinic acid-triphenylphosphine complex under nitrogen protection for 4min. The reaction is continued for 4h. After the reaction is completed, distill at 120°C under reduced pressure for 2h to obtain the organosilicon modifier.
[0071] Comparative Example 6
[0072] A method for preparing an inorganic nano-ceramic coating is substantially the same as that of Example 6, except that the organosilicon modifier added in step (2) is replaced by an equal weight of an organosilicon modifier prepared by the following method:
[0073] Add 1500g of toluene to the reactor, stir, raise the temperature to 90°C, add 900g of high hydrogen silicone oil and 450g of 4-propyleneoxy-2-hydroxybenzophenone in sequence, and slowly add 20g of chloroplatinic acid-triphenylphosphine complex under nitrogen protection for 4min. After the addition, react for 4h, and distill at 120°C under reduced pressure for 2h to obtain the organosilicon modifier.
[0074] The high hydrogen silicone oil used in the examples and comparative examples of the present application is Dow Corning high hydrogen silicone oil MHX-1107 (20cs); the talc powder specification is 1250 mesh; the mica powder specification is 400 mesh; the kaolin specification is 800 mesh; the acidic silica sol model is HA2005, purchased from Shandong Better New Materials Co., Ltd.
[0075] The chloroplatinic acid-triphenylphosphine complex used in the examples and comparative examples of the present application is an isopropanol suspension with a molar concentration of 0.05 M, and the molar ratio of chloroplatinic acid to the triphenylphosphine complex is 1:1. The specific preparation method is: take 20.0 ml of a 0.1 M chloroplatinic acid isopropanol solution, add it to an equal volume and equimolar triphenylphosphine isopropanol solution, mix well, and obtain a 0.05 M chloroplatinic acid-triphenylphosphine complex.
[0076] Refer to GB / T23443-2009 Aluminum veneer for architectural decoration, and conduct performance tests on the ceramic coating, such as appearance quality, pencil hardness test, adhesion test (dry type), chemical corrosion resistance (resistance to hydrochloric acid and nitric acid), and anti-aging. Refer to GB / T21866-2008 to test the antibacterial performance of the coating.
[0077] Table 1
[0078]
[0079] It can be seen from Table 1 that the inorganic nano-ceramic coating prepared in the present application has high hardness, good acid resistance, strong adhesion, high anti-aging performance and good antibacterial performance.
[0080] Comparative Example 1 is a comparative example without adding an organosilicon modifier. From the data in Table 1, it can be seen that its gloss retention rate is 50.2%, the antibacterial property is 65.4%, and the anti-aging performance and antibacterial and mildew-proof properties are poor.
[0081] Comparative Example 2 is a comparative example in which the organosilicon modifier is replaced with 0.25g of high hydrogen silicone oil, 0.16g of dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium and 0.14g of 4-propyleneoxy-2-hydroxybenzophenone. It can be seen from the data in Table 1 that the gloss retention rate is 85.6%, the antibacterial property is 88.6%, and the anti-aging performance and antibacterial and mildew resistance are average.
[0082] Comparative Example 3 is a comparative example in which the organosilicon modifier is replaced with Silok 3300 amino-functional organosilicon prepolymer. It can be seen from the data in Table 1 that after 4000 hours, the gloss retention rate is 54.3%, the antibacterial property is 50.1%, and the anti-aging performance and antibacterial and mildew-proof performance are poor.
[0083] Comparative Example 4 is a room temperature cured, ultra-weatherable, high-hardness, and wear-resistant water-based inorganic nano-ceramic coating prepared using the raw materials and methods of Example 2 in Publication No. CN109266057A. It can be seen from the data in Table 1 that the gloss retention rate is 60.1%, the antibacterial property is 52.6%, and the anti-aging performance and antibacterial and mildew-proof properties are poor.
[0084] Comparative Example 5 is a comparative example of an organosilicon modifier without grafting 4-propyleneoxy-2-hydroxybenzophenone. From the data in Table 1, it can be seen that the gloss retention rate is 52.3%, the antibacterial property is 80.8%, and the anti-aging performance is poor.
[0085] Comparative Example 6 is a comparative example of an organosilicon modifier of ungrafted dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethylammonium. From the data in Table 1, it can be seen that the gloss retention rate is 80.9%, the antibacterial property is 66.3%, and the antibacterial and mildew proof performance is poor.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. An inorganic nano-ceramic coating, characterized in that: The invention comprises the following raw materials in parts by weight: Water-based inorganic nano-ceramic emulsion: 50-80 parts, Pigment: 0.5-1 part, Filling: 8-10 parts, Defoaming agent: 0.1-0.5 parts, Dispersant: 1-3 parts, Wetting agent: 0.2-0.4 parts, Film-forming aid: 3-5 parts, Deionized water: 20-60 parts; The aqueous inorganic nano-ceramic emulsion comprises the following raw materials in parts by weight: Silica sol: 20-80 parts, Silane: 10-50 parts, Silicone modifier: 0.3-0.8 parts, Surfactant: 0.5-1 part, Deionized water: 30-50 parts; The organosilicon modifier is prepared by the following method: Add toluene to the reactor, stir, heat to 70-110°C, add high hydrogen silicone oil and dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethyl ammonium in sequence, slowly drop chloroplatinic acid-triphenylphosphine complex under nitrogen protection, react for 2-6h after the addition is complete, cool to 50°C, then add 4-propyleneoxy-2-hydroxybenzophenone, heat to 80-100°C, react for 4-8h, and after the reaction is completed, distill under reduced pressure at 110-130°C to obtain an organosilicon modifier; The dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethylammonium is prepared by the following method: Add 120g of chloroacetic acid to the reaction bottle, heat it to 100℃ and melt it, then add 100g of 2-methoxy-5-(prop-2-enyl)phenol and 1g of 98.3wt% concentrated sulfuric acid, then heated to 120°C, reacted for 10h, washed with deionized water three times after the reaction, using 50g deionized water each time, then dissolved with 20ml dichloromethane, dried with 40g anhydrous Na2SO4, and then distilled at 45°C under reduced pressure for 5h to obtain a light yellow intermediate; 10g of the light yellow intermediate and 30g of dichloromethane were added to a reaction flask, 8g of dodecyldimethyl tertiary amine was slowly added dropwise for 5min, refluxed for 5h after the addition, and then distilled at 40°C under reduced pressure for 4h, and then recrystallized with an acetone / ethanol mixed solution, the mixed volume ratio of acetone to ethanol in the acetone / ethanol mixed solution was 9:1, repeated 3 times, using 100ml of the mixed solution each time, and vacuum dried at 60°C for 5h to obtain dodecyl (2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl) dimethylammonium.
2. The inorganic nano-ceramic coating according to claim 1, characterized in that: The mass ratio of the toluene, high hydrogen silicone oil, dodecyl(2-{[2-methoxy-5-(prop-2-enyl)phenyl]oxy}-2-oxyylideneethyl)dimethylammonium, chloroplatinic acid-triphenylphosphine complex, and 4-propyleneoxy-2-hydroxybenzophenone is 15:(8-10):(5-7):(0.1-0.3):(3-6).
3. The inorganic nano-ceramic coating according to claim 1, characterized in that: The pigment is one of titanium dioxide, lead chrome yellow and iron blue.
4. The inorganic nano-ceramic coating according to claim 1, characterized in that: The filler is one or a combination of talcum powder, mica powder and kaolin.
5. The inorganic nano-ceramic coating according to claim 1, characterized in that: The defoamer is one of BYK-024 defoamer, TEGO Foamex 830 defoamer and BYK-055.
6. The inorganic nano-ceramic coating according to claim 1, characterized in that: The dispersant is one of LD-64190 and LD-6408.
7. The inorganic nano-ceramic coating according to claim 1, characterized in that: The wetting agent is Digo 270 wetting agent, the film-forming aid is silane coupling agent KH-550, and the silica sol is acidic silica sol.
8. The inorganic nano-ceramic coating according to claim 1, characterized in that: The silane is a combination of one or more of phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
9. The inorganic nano-ceramic coating according to claim 1, characterized in that: The surfactant is at least one of the quaternary ammonium cationic surfactants 1831 and OB-2.
10. A method for preparing the inorganic nano-ceramic coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Add silane, surfactant and organosilicon modifier to the stirrer in sequence, stir for 10-20 minutes, and after mixing evenly, form a transparent silane mixed liquid; then add silica sol and stir for 10-30 minutes; slowly raise the temperature to 30-50°C, stir at a constant temperature for 2-8 hours, stop stirring, keep warm at 40°C for 1-4 hours, then add deionized water, mix evenly and cool to room temperature to obtain an inorganic nano-ceramic emulsion; (2) The inorganic nano-ceramic emulsion prepared above is mixed with pigment and filler, dispersed at high speed for 20-40 minutes using a high-speed disperser, and then ground using a horizontal sand mill. After grinding, a dispersant, a defoamer, a wetting agent, a film-forming aid and deionized water are added and stirred evenly to obtain an inorganic nano-ceramic coating.
Citation Information
Patent Citations
Corrosion-proof anti-ultraviolet paint and method for manufacturing the same
CN101200613A
Normal temperature cured super weather-resistant and wear-resistant high-hardness water-based inorganic nanoceramic coating and preparation method thereof
CN109266057A
Long-acting antibacterial agent, silicone rubber and preparation method thereof
CN115975203A